PENGARUH KOSENTRASI DAN WAKTU PEMBERIAN LIMBAH CAIR PKS TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KACANG PANJANG (Vigna sinensis L.) - Herry Harianto, Abdul Fatah, dan Hery Sutejo (Universitas 17 Agustus 1945 Samarinda, 2014)
The objective of research was to study the effect of concentration and application of palm oil effluent on the growth and production of long bean. The research was carried out from March to June 2013, at Sebelang Village of Muara Pahu Sub-District, West Kutai Regency. The Randomised Block Design was employed for the research with factorial 3 x 3 and 3 replications. The first factor was Liquid Palm Oil Effluent Concentration (D) consisted of 3 sub-factors: 1 ml/crop (d1), 2 ml/crop (d2), and 3 ml/crop (d3). And the second factor was time of application (W): 10 days after sowing (w1), 20 days after sowing (w2), and 30 days after sowing (w3). Results of the research revealed that: (1) the liquid palm oil effluent concentration did not affect significantly on the crop length at 13, 23, and 33 days, age of crop flowered, age of harvest, number of fruit per crop, fruit length, and production per crop; (2) the time of application did not also affect significantly all parameters observed, namely crop length, age of crop flowered, age of harvest, number of fruit per crop, fruit length, and production per crop; and (3) the interaction between the two above factors also did not affect significantly on all parameters observed.